2006
DOI: 10.1364/josab.23.002518
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence from Au nanoparticles embedded in Au:oxide composite films

Abstract: Au:oxide composite multilayer films with Au nanoparticles sandwiched by oxide layers (such as SiO 2 , ZnO, and TiO 2) were prepared in a magnetron sputtering system. Their photoluminescence (PL) spectra were investigated by employing a micro-Raman system in which an Argon laser with a wavelength of 514 nm was used as the pumping light. Distinct PL peaks located at a wavelength range between 590 and 680 nm were observed in most of our samples, with Au particle size varying from several to hundreds of nanometers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 22 publications
2
36
0
Order By: Relevance
“…Generally, the inherent large nonlinear optical response of a dielectric hosts (glass, polymers, etc.) may be enhanced by several folds by insertion of small metal clusters [41]. The molar polarizability (as calculated from Lorentz Lorenz equation) and refractive index of KBS antimony glass of the present study are found to be 9.598 Å 3 and 1.947 respectively.…”
Section: Resultsmentioning
confidence: 45%
“…Generally, the inherent large nonlinear optical response of a dielectric hosts (glass, polymers, etc.) may be enhanced by several folds by insertion of small metal clusters [41]. The molar polarizability (as calculated from Lorentz Lorenz equation) and refractive index of KBS antimony glass of the present study are found to be 9.598 Å 3 and 1.947 respectively.…”
Section: Resultsmentioning
confidence: 45%
“…In silver nanoparticles, the radiative recombination of electron hole pair between d-band and sp-conduction above the Fermi level produces emission [12][13][14][15][16][17], which occurs practically at 470 nm when excited with 350 nm of optical source. Moreover, the absorbed linoleic acid during the formation of silver nanoparticles further enhances the intensity of emission [12][13][14].…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
“…polymers, silicon dioxide, oxynitride layers, etc.) for creation of the nanocomposite films, which are of importance because of their unusual nonlinear optical and electrical properties [7,8]. Evidently, the properties of nanocomposites will depend on the size, density, and the position of Au NPs [9].…”
Section: Introductionmentioning
confidence: 99%